Local Conflict and Development Projects in Indonesia : Part of the Problem or Part of a Solution? - Barron, Patrick; Diprose, Rachael; Woolcock, Michael (World Bank, Washington, DC, 2012)
Drawing on an integrated mixed methods research design, the authors explore the dynamics of the development-conflict nexus in rural Indonesia, and the specific role of development projects in shaping the nature, extent, and trajectories of "everyday" conflicts. They find that projects that give inadequate attention to dispute resolution mechanisms in many cases stimulate local conflict, either through the injection of development resources themselves or less directly by exacerbating preexisting tensions in target communities. But projects that have explicit and accessible procedures for managing disputes arising from the development process are much less likely to lead to violent outcomes. The authors argue that such projects are more successful in addressing project-related conflicts because they establish direct procedures (such as forums, facilitators, and complaints mechanisms) for dealing with tensions as they arise. These direct mechanisms are less successful in addressing broader social tensions elicited by, or external to, the development process, though program mechanisms can ameliorate conflict indirectly through changing norms and networks of interaction.